Approach to cognitive and methodological integration in comparative studies between Sharia and law - NAIMI , Abdelmounaime (Journal of Social Sciences and Humanities, 2025)
Comparative studies between Sharia sciences and legal sciences occupy their place among the studies related to the humanities, as they are unique in a number of characteristics that distinguish them from others, and given the intersection of these studies in many cognitive and methodological aspects, they open the way for researchers and scholars to direct their scientific work towards revealing the aspects of cognitive and methodological integration of comparative studies between Sharia and law, in terms of formation, framing or academic scientific research. In this context, this study aims to reveal the features of integration and knowledge in this type of studies, which combines two branches of the humanities, namely Islamic law and positive law, according to a cognitive and methodological approach, based on a specific research plan that we reach with its commitment to record the most important possible outputs in this regard.